A comparison analysis of smart phone competition model: Korean case and Japanese case - Masashi Ueda; Yousin Park; Yunju Chen (International Telecommunications Society (ITS), 2012)
This paper investigated the driving force of diffusion in smart phone market by analysing usage of them and making their component model. Main findings are following four: 1) In Korea and Japan their average smart phones' traffic per user has been the world's highest level. But its diffusion pattern is very different. 2) The Korean government and private companies strongly support diffusion of smart phones but not so much in Japan. 3) Korean and Japanese Mobile phone companies and/or manufacturers try to build their application stores. They collect funds for developing tools and application developers. 4) Importance of customises or localise for drastic diffusion.
Keywords: L22; L21; 330; Smartphone; diffusion pattern; path dependency; Component Model.